Migration and non-breeding season movements of satellite-tracked Levant Sparrowhawk Accipiter brevipes. (8th June 2021) - Yang, Chien-Hung; Bildstein, Keith; Tumanyan, Siranush; McGrady, Michael
Abstract : In 2013, we satellite-tracked four juvenile Levant Sparrowhawks Accipiter brevipes from their nests in southern Armenia. Mean departure date from summering areas was 30 August. During autumn, birds migrated toward Africa along both the east and west coasts of the Red Sea. One bird was tracked to its wintering area in Tanzania in two successive years, moving nomadically in both years. The areas used during the winters of 2013/2014 and 2014/2015 overlapped to some extent in eastern Tanzania, though the former was generally farther south. Migration north by this bird commenced during the second half of February; it flew to its summering grounds via Sinai. This study provides the first details of the entire migration cycle of an individual of this species, and its movements during the non-breeding season.